Influence of Allium sativum on Pharmacodynamics and Pharmacokinetics of Gliclazide in Normal Rabbits (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: In this chapter, the influence of selected dose of Allium sativum (84 mg/1.5 kg bd.wt) on the pharmacodynamicsand pharmacokinetics of selected dose of gliclazide (5.6 mg/1.5 kg bd.wt) was studied in normal rabbits. Materials andMethods: Materials required were purchased from Sai Chemicals, Visakhapatnam, India. Inbred adult Wistar rabbitsof either sex were used for the study. Gliclazide (TD) was administered orally to all the rabbits. After a wash out periodof 1 week, the same groups of animals were administered with Allium sativum (84 mg/1.5 kg bd.wt.) orally. Again aftera further washout period of 1 week, the same group was administered with A. sativum (84 mg/1.5 kg bd.wt.) orally,30 min before the administration of gliclazide (5.6 mg/1.5 kg bd.wt). Blood samples were withdrawn at 0, 1, 2, 3, 4, 6,8, 12, 16, 20, and 24 h intervals from marginal ear vein puncture and were analyzed for blood glucose by GOD/PODmethod in all the experiments and serum gliclazide. Results: A. sativum has found to enhance the hypoglycemic effectof gliclazide. There was a considerable percent blood glucose reduction with gliclazide (5.6 mg/1.5 kg bd.wt) beforeand after treatment with Allium sativum (104 mg/kg) in rabbits.Conclusion: The interaction between A. sativum andgliclazide appears to be pharmacodynamic and pharmacokinetic in nature.